Influence of sowing environments on yield of sesame genotypes under shifting weather conditions of Deccan Plateau (Telangana): INFLUENCE OF SOWING ENVIRONMENTS AND GENOTYPES ON SESAME YIELD - RATNAKUMAR PASALA; KULASEKARAN RAMESH (Journal of Oilseeds Research, 2019)
Climate change poses a challenge to sustainability of agricultural ecosystems and in turn the social and economic development, livelihoods of communities in the world and India is no exception. Sesame is an important oilseed crop that has nutritional components such as lignans (antioxidant), sesamol along with tocopherols. This crop is grown under varied climatic conditions in the country even though it is highly sensitive to thermal regimes. Therefore, identifying or breeding sesame varieties with adaptation to wider ecological regions with high yield potential is the need of the hour. To identify high yielding sesame genotypes under shifting weather conditions of Deccan Plateau, an experiment was conducted with different dates of sowing. The sowing dates were designed in such a way that it considered the present cropping situation where it is grown after the harvest of the kharif crop. A set of popular farmer preferred sesame varieties that are generally grown in different sesame growing regions of the country viz., GT 10, GT 3, GT 4, RT 346, RT 351, Swetha til, YLM 66 and CUMS 17 were selected for the study. Among them, GT 10 performed better under October sowing under agro-ecological regions of Telangana while GT3, GT 4, RT 346, RT 351, Swetha til, YLM 66 and CUMS 17 recorded maximum seed yield with November sowing. Among the genotypes, CUMS 17 recorded the maximum seed yield during both October and November sowings. If a farmer has a choice of sowing rabi crop immediately after the harvest of kharif crop, he may opt for late rabi sowing area of Telangana with GT 10. In case there is a delay, choose other varieties to harvest maximum seed yield.